Strategic organizational alignment : authority, power, results - Crosby, Chris (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2017)
Business results, major change, project initiatives--can be achieved more easily than imagined. Strategic Organizational Alignment shows you how and points out the reasons why most excuses businesses make for inadequate implementations are wrong. Through stories, illustrations, and step-by-step guides Crosby shows you a simple, profound, and repeatable way to ensure your business aligns its employees and has a clear path to success.
Story 1. The story of Joe, Ed, and Jane begins. Chapter 1. Authority -- Story 2. What are we working towards? Chapter 2. Goals -- Story 3. The conversation continues. Chapter 3. Sponsor/agent/target/advocate -- Story 4. The adventure gets real. Chapter 4. Power -- Story 5. Help me understand. Chapter 5. SATA workplace examples -- Story 6. Our situation is unique. Chapter 6. SATA analysis -- Story 7. A great beginning but. Chapter 7. Accountability -- Story 8. What am I missing? Chapter 8. Structure -- Story 9. A major glitch. Chapter 9. Workplace knowledge -- Story 10. Why are things still choppy? Chapter 10. Follow-up -- Story 11. More road blocks. Chapter 11. SATA common mistakes -- Story 12. Analysis paralysis. Chapter 12. Decision making -- Story 13. Now we can move. Chapter 13. Employee empowerment -- Story 14. Do I have to, really? Chapter 14. Adult development -- Story 15. This is what success feels like -- Appendix A. SATA assessments -- Appendix B. Project manager SATA role -- Appendix C. Structure assessment -- Appendix D. Additional SATA example -- Appendix E. My organization development (OD) roots -- Chapter index -- Bibliography.
Includes bibliographical references (page [257]) and index.
Title from PDF title page (viewed on November 5, 2016).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Management; Organization; Organizational behavior; alignment; business results; change; change management; cross-functional; leadership; MBA; organization development; organizational development; productivity; project management; stanford; workplace; Electronic books